Modelling distribution and associated environmental preferences of South African kelps and their close relatives - Lutchminarayan, Kirtanya (Department of Biological Sciences, 2018)
Kelp are central components of marine ecosystems that are found on the west coast of South Africa and in temperate regions around the world. They are ecologically important in providing vertical habitats, and sustaining diverse life-forms. The kelp species that are investigated in this study are Ecklonia cava, Ecklonia maxima, Ecklonia radiata, Laminaria pallida and Laminaria ochroleuca. Ecklonia maxima, E. radiata and L. pallida are dominant South African kelps, therefore studying these species provides information about their distributions and environmental preferences. E.cava and L. ochloleuca are of interest as they are close relatives to South African kelp species, and add to the understanding of Ecklonia and Laminaria in a more global context. The aims of this study were to map the biogeographical distribution of each species, and model their potential niches based on the environmental conditions that facilitate their growth. Species Distribution Modelling was used to map the fundamental niche of each species. The Maxent method was used to model predictive niches by layering known coordinates of where each species is found, along with the Bio-ORACLE dataset of 23 environmental variables, consisting of satellite and in-situ data. The Carto cloud computing platform was used to map the current distribution of each species. The major environmental predictors of each species distribution were identified in the modelling process and contributed to the final predicted habitat suitability maps. The results of this study show that Maxent identified maximum, minimum, mean and range in sea surface temperature to be associated with all species' distribution. Measures of irradiance or light availability (specifically Photosynthetically Active Radiation, Diffuse Attenuation and cloud cover), were important predictors of four of the species' distributions. Chlorophyll, a proxy for nutrients, emerged as an important correlate of most distributions, whilst silicate, phosphate and calcite were important, particularly to the distribution of kelp species found outside of South Africa. There were regions identified 7 where each species could potentially grow, but are not found. The results show that while E.maxima and L.pallida are distributed along the west coast of southern Africa, L.pallida could potentially grow along the west coast of South America, whilst E.maxima appears to have a niche endemic to South Africa. Ecklonia radiata is distributed along the south coast of South Africa as well as southern Australia, New Zealand, whilst it could potentially grow in the north Atlantic, northeast Pacific and southeast Pacific. Ecklonia cava's distribution is endemic to the Japanese and South Korean coast and is predicted to be able to spread down the coast of China. Laminaria ochroleuca is distributed along the coasts of Spain, Portugal, France and Northern Africa with a widespread distribution on the British coastline, with a predicted potential to extend to western Ireland. Other suitable habitats for L.ochroleuca were southern Australia and New Zealand. Ecklonia maxima and L.pallida have overlapping distributions, whilst all other species have different distributions. The ecological preferences of each of these species differed in parameter, but were related to the same variables; temperature, light and nutrients. The South African species, E.maxima, E.radiata and L.pallida, differed in their preferences, including those occupying the same coastline. All species of kelp had variably unique distributions and varying environmental preferences compared to their congenerics. The possible causes for species not being able to grow in identified niches are likely to be temperature limits, light and nutrient limits, physical barriers and limitations to movement and establishment, as well as geographical and associated evolutionary adaptations that may limit dispersal. Besides the environmental variables analysed, biological, oceanographic and in-situ data is deemed important in gaining a complete and causal understanding of species distributions and their drivers. This study provides insight into South African kelp systems and their close relatives in a global context, and shows the successful use of niche modelling methods that can be more widely applied in marine research, conservation and management